Posterior communicating artery vasospasm impairs cerebral pulsatility in an experimental subarachnoid hemorrhage model - Daltaban, İskender Samet and Gel, Mehmet Selim and Kanat, Ayhan and Aydın, Mehmet Dumlu and Turğut, Songül (Frontiers in Neurology, 2025)
BackgroundSubarachnoid hemorrhage (SAH) commonly causes cerebral vasospasm and delayed ischemia. Spasm of the posterior communicating artery (PCoA) can disrupt cerebral hemodynamics. We assessed its effect on cerebral pulsatility in a rabbit SAH model, focusing on intracranial pressure pulse amplitude as an early, sensitive marker of vasospasm-driven change, whereas global CBF or neurological outcomes generally require larger or longer studies.MethodsRabbits were randomly assigned to three groups: control (no injection), sham-controlled (saline injection), and SAH (0.75 mL autologous blood injection into the basal subarachnoid space near the PCoA under anesthesia). Heart rate and cerebral pulsation amplitude (measured via intracranial pressure transducer) were recorded on day 1 and day 7. On day 7, animals were euthanized, and histological analysis of the PCoA was performed. Vasospasm index (VSI) was calculated as the ratio of arterial wall area to lumen area. Group comparisons and temporal changes were assessed statistically.ResultsTwenty-three rabbits completed the study (five control, five sham-controlled, 13 SAH, two SAH animals excluded due to early mortality). On day 1, the SAH group showed a significantly reduced pulsation amplitude compared to controls and sham-controlled groups. By day 7, pulsation amplitude partially recovered in the SAH group but remained lower than in controls. Control and sham-controlled groups exhibited a slight, non-significant decline in pulsation. The VSI was highest in the SAH group, moderate in sham-controlled, and lowest in the control groups. Heart rate declined over time across all groups, with significant bradycardia in the SAH group by day 7.ConclusionPCoA vasospasm following experimental SAH results in a sustained reduction in cerebral pulsatility. These findings suggest that localized vasospasm disrupts pulsatile intracranial dynamics, potentially contributing to SAH-related pathophysiology.